PENGARUH KOLONIAL DI NUSANTARA - Naniek Harkantiningsih (Badan Riset dan Inovasi Nasional, 2014)
Colonial Influence in Nusantara. Archipelago is a source of spices and other natural products, in this time the commodity highly sought by Asian and European nations. In the 16th Century of the archipelago waters began explored European merchant ships, the strength of Europe’s shipping and trade dominate Southeast Asian waters, including the archipelago until the mid 20th Century, was marked by the arrival of the Japanese colony. This is where the role of the commencement of the foreign colony in the archipelago. Expedition, commercial activity, and they do politics can be traced through historical records and archaeological evidence, so many and scattered in the archipelago. In this paper, will specifically address the colonial traces in several places in the archipelago. Exploratory and descriptive stages in the collection and processing of data, then look at the pattern of spreading and compare the character and chronology of colonial archaeological evidence found. The existence of the source of the spice, in the archipelago, can be attributed not only as evidence of trade links between producer and consumer, but also as evidence of the existence of the foreign community in the archipelago. Span of the history of the foreign colony in the archipelago long enough for more than three centuries. In periods in which the role and orientation of their activities, can be seen clearly based on the object of study, character, pattern of distribution, function and chronology of the existence of the foreign colony in the archipelago. Nusantara merupakan sumber rempah-rempah dan hasil alam lainnya, pada masanya komoditi tersebut sangat dicari oleh bangsa Asia dan Eropa. Sekitar abad ke-16 M. perairan Nusantara mulai dijelajahi kapal-kapal dagang Eropa, kekuatan pelayaran dan perdagangan Eropa ini mendominasi perairan Asia Tenggara termasuk Nusantara hingga pertengahan abad ke- 20 M., ditandai dengan kedatangan koloni Jepang. Dari sinilah dimulainya peranan koloni asing di Nusantara. Ekspedisi, aktivitas komersial, dan politik yang mereka lakukan dapat ditelusuri melalui catatan sejarah dan bukti arkeologi, yang banyak dan tersebar di Nusantara. Dalam tulisan ini, secara khusus akan membahas jejak peninggalan kolonial di beberapa tempat di Nusantara. Tahapan eksplorasi dan deskriptif dalam pengumpulan dan pengolahan data, kemudian melihat pola persebarannya dan membandingkan karakter serta kronologi bukti-bukti arkeologi kolonial yang ditemukan. Keberadaan sumber rempah-rempah, di Nusantara, dapat dikaitkan bukan hanya sebagai bukti adanya jaringan perdagangan antara negara produsen dan konsumen, tetapi juga sebagai bukti keberadaan komunitas asing di wilayah Nusantara. Rentang waktu sejarah koloni asing di Nusantara lebih dari tiga abad. Dalam periode dimana peran dan orientasi kegiatan mereka, dapat diketahui secara jelas berdasarkan obyek kajian, karakter, pola persebaran, fungsi dan kronologi keberadaan koloni asing di Nusantara.